Llama and sheep ruminal fluid digestive capacity by in vitro gas production technique - Ortiz Chura, Abimael (2022)
BACKGROUND: The in vitro gas production technique has been used to evaluate forage fermentation kinetics. However, individual and animal species variation can change fermentation patterns due to differences in ruminal environment and microbiota. The aim was to verify whether rumen inoculum (RI) of llama had superior intrinsic digestion capacity and reduced methane (CH4) production compared to sheep RI using fescue and paspalum hay as substrates. RESULTS: Dry and organic matter (OM) digestibility produced with llama RI tended to exceed that of sheep (P = 0.099 and 0.074, respectively) at 24 h of incubation. However, at 48 h, the sheep RI presented higher substrate digestibility and asymptotic value of gas production than that of llama (P < 0.010). CH4 production showed no differences between RI or substrates (P > 0.050). The NH3-N and total volatile fatty acid concentrations were greater in the RI of llamas compared to those of sheep (P < 0.050). Acetate and butyrate proportions and acetate-to-propionate ratio were greater in the RI of llamas compared to those of sheep (P < 0.001) at 24 and 48 h. However, propionate proportion was greater in sheep compared with llama (P < 0.001). CONCLUSION: Llama RI tended to surpass that of sheep in dry and OM digestibility at 24 h of incubation, but sheep RI at 48 h presented a higher digestibility and gas production value than llama RI. No differences between the two species were detected for CH4 production. This study showed that llama RI did not perform better than sheep RI in digesting low-quality forages.